Exponential Stability for the Schlogl System by Pyragas Feedback - Gugat, Martin; Mateos, Mariano; Troeltzsch, Fredi (Vietnam Journal of Mathematics, 2020)
The Schlogl system is governed by a nonlinear reaction-diffusion partial differential equation with a cubic nonlinearity. In this paper, feedback laws of Pyragas-type are presented that stabilize the system in a periodic state with a given period and given boundary traces. We consider the system both with boundary feedback laws of Pyragas type and distributed feedback laws of Pyragas and classical type. Stabilization to periodic orbits is important for medical applications that concern Parkinson's disease. The exponential stability of the closed loop system with respect to the L-2-norm is proved. Numerical examples are provided.
CRIS-Team WoS Importer:2020-03-13